Editorial: latent class analysis to improve confidence in the diagnosis of IBS. Issue 9 (3rd April 2017) - Ballou, S.; Lembo, A.
Abstract : Linked Content This article is linked to Sood et al papers. To view these articles visithttps://doi.org/10.1111/apt.14012 andhttps://doi.org/10.1111/apt.13949 .